Understanding the Flash Sintering of Rare‐Earth‐Doped Ceria for Solid Oxide Fuel Cell. Issue 6 (4th March 2015) - Jiang, Taizhi; Wang, Zhenhua; Zhang, Jing; Hao, Xiaoming; Rooney, David; Liu, Yajie; Sun, Wang; Qiao, Jinshuo; Sun, Kening; Hay, R.
<x xml:space="preserve">Abstract</x> A novel electrical current applied technique known as flash sintering has been applied to rapidly (within 10 min) densify electrolytes including Ce0.8Gd0.2O1.9 (GDC20), Ce0.9Gd0.1O1.95 (GDC10), and Ce0.8Sm0.2O1.9 (SDC20) for application in Solid Oxide Fuel Cells (SOFCs). The densification temperature for the three electrolytes was 554°C, 635°C, and 667°C, respectively, which is far below conventional sintering temperatures. All specimens after flash sintering maintained the pure fluorite structure and exhibited a well‐densified microstructure. To investigate the flash‐sintering mechanism, we have applied Joule heating effect with blackbody radiation theory, and found that this theory could reasonably interpret the flash‐sintering phenomenon by matching theoretically calculated temperature with the real temperature. More importantly, one of the materials inherent properties, the electronic conductivity, has been found correlated with the onset of flash sintering, which indicates that the electrons and holes are the primary current carriers during the start of flash‐sintering process. As a result, potential densification mechanisms have been discussed in terms of spark plasma discharge.